2023
DOI: 10.1093/texcom/tgad009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of distributions reveals real differences on dichotic listening scores between left- and right-handers

Abstract: About 95% of right-handers and 70% of left-handers have a left-hemispheric specialization for language. Dichotic listening is often used as an indirect measure of this language asymmetry. However, while it reliably produces a right-ear advantage (REA), corresponding to the left-hemispheric specialization of language, it paradoxically often fails to obtain statistical evidence of mean differences between left- and right-handers. We hypothesized that non-normality of the underlying distributions might be in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In our study, negative effect sizes were found for the scales "Hallucination" and for "Positive formal thought disorder", indicating higher symptom severity in schizophrenia patients with an increased tendency towards left-handedness. Since left-handed individuals are more likely to show atypical right-sided language lateralization [69], this finding suggests that handedness may be a relevant factor for the relation of schizophrenia and language lateralization that should be considered in future studies.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, negative effect sizes were found for the scales "Hallucination" and for "Positive formal thought disorder", indicating higher symptom severity in schizophrenia patients with an increased tendency towards left-handedness. Since left-handed individuals are more likely to show atypical right-sided language lateralization [69], this finding suggests that handedness may be a relevant factor for the relation of schizophrenia and language lateralization that should be considered in future studies.…”
Section: Discussionmentioning
confidence: 90%
“…1). Instructed to report the stimulus heard best, participants typically report the right-ear stimulus more frequently than the leftear stimulus when a verbal stimulus material like words or syllables is used (e.g., Bless et al, 2015;Karlsson, Hugdahl, Hirnstein, & Carey, 2023;Parker, Woodhead, Thompson, & Bishop, 2021). This right-ear advantage (REA) is traditionally interpreted to reflect the dominance of the left cerebral hemispheres for speech and language processing (e.g., Bryden, 1988;Carey & Johnstone, 2014;Hugdahl & Westerhausen, 2016;Kimura, 1967;Westerhausen & Kompus, 2018;Wexler, 1988).…”
Section: Introductionmentioning
confidence: 99%